In vitro inhibition of acetylcholinesterase activity by yellow field pea (Pisum sativum) protein-derived peptides as revealed by kinetics and molecular docking - Asen, Nancy D.; Okagu, Ogadimma D.; Udenigwe, Chibuike C.; Aluko, Rotimi E. (Frontiers in Nutrition, 2022)
Compounds with structural similarities to the neurotransmitter (acetylcholine) are mostly used to inhibit the activity of acetylcholinesterase (AChE) in Alzheimer’s disease (AD) therapy. However, the existing drugs only alleviate symptoms of moderate to mild conditions and come with side effects; hence, the search is still on for potent and safer options. In this study, HPLC fractionations of AChE-inhibitory pea protein hydrolysates obtained from alcalase, flavourzyme and pepsin digestions were carried out followed by sequence identification of the most active fractions using mass spectrometry. Subsequently, 20 novel peptide sequences identified from the active fractions were synthesized and five peptides, QSQS, LQHNA, SQSRS, ETRSQ, PQDER (IC50 = 1.53 – 1.61 μg/mL) were selected and analyzed for ability to change AChE protein conformation (fluorescence emission and circular dichroism), kinetics of enzyme inhibition, and enzyme-ligand binding configurations using molecular docking. The kinetics studies revealed different inhibition modes by the peptides with relatively low (< 0.02 mM and < 0.1 mM) inhibition constant and Michaelis constant, respectively, while maximum velocity was reduced. Conformational changes were confirmed by losses in fluorescence intensity and reduced α-helix content of AChE after interactions with different peptides. Molecular docking revealed binding of the peptides to both the catalytic anionic site and the peripheral anionic site. The five analyzed peptides all contained glutamine (Q) but sequences with Q in the penultimate N-terminal position (LQHNA, SQSRS and PQDER) had stronger binding affinity. Results from the different analysis in this study confirm that the peptides obtained from enzymatic digestion of pea protein possess the potential to be used as novel AChE-inhibitory agents in AD management.